Influence of gas-release strategies on the production of biohydrogen and biobutanol in ABE fermentation. Issue 1 (2nd January 2022) - Stein, Ullrich Heinz; Abbasi-Hosseini, M.; Kain, J.; Fuchs, W.; Bochmann, G.
Abstract: This research reports on the effect of three gas release strategies in acetone–butanol–ethanol fermentations using two Clostridium acetobutylicum (DSMZ 792, DSMZ 1731) and one Clostridium beijerinckii strain (DSMZ 6422). The influences of three different gas release strategies (constant gas release, interval gas release and no gas release) on the simultaneous production and yield of biohydrogen and biobutanol were investigated. In general, the three gas release strategies induced different pressure profiles which altered the spectrum of the end products. In fermentation conducted under overpressure, the yield of butanol increased, except for Clostridium acetobutylicum DSMZ 792 which maintained a stable and high butanol yield throughout all conducted fermentations. The volumetric butanol productivity was lowered by 17.2%, 20.0% and 11.1% for DSMZ 6422, DSMZ 1731 and DSMZ 792, respectively, when the produced hydrogen-rich gas was not released throughout the fermentation. Volumetric hydrogen production rates dropped simultaneously in all tested Clostridium strains, by almost 60%, when gas was not released. Clostridium acetobutylicum (DSMZ 792) under constant gas release (DSMZ 792) showed the best results concerning butanol and hydrogen productivity. If higher butanol yield is targeted, application of overpressure is recommended as it increased the yield for DSMZ 6422 and DSMZ 1731 by 23.3% and 10.0%, respectively. Highlights: Overpressure conditions generally increase butanol yields and reduce hydrogen yields Ambient pressure leads to highest volumetric productivity of hydrogen and butanol in all strains Clostridium acetobutylicum (DSMZ 792) shows most promising results